Spatiotemporal imaging of electrocatalytic activity on single 2D gold nanoplates via electrogenerated chemiluminescence microscopy. Issue 15 (15th March 2019) - Chen, Ming-Ming; Zhao, Wei; Zhu, Meng-Jiao; Li, Xiang-Ling; Xu, Cong-Hui; Chen, Hong-Yuan; Xu, Jing-Juan
Abstract : Spatiotemporal resolved electrocatalytic activity on single 2D gold nanoplates was imaged via electrogenerated chemiluminescence microscopy. Abstract : Uncovering the relationship between the structure, surface properties and electrochemical activity of nanoparticles is of great importance for constructing novel nanocatalysts and highly efficient electrocatalytic devices. Here we report a study of the heterogeneously distributed electrocatalytic activity on individual 2D gold nanoplates. On the basis of electrogenerated chemiluminescence (ECL) microscopy, the size, shape, and site-specific catalytic activity of 2D nanocrystals could be directly imaged at the single particle level with submicron resolution. Since the microelectrode effect with higher fluxes at the perimeter was offset by diffusion of excited species of Ru(bpy)3 2+, calculated by finite element simulation, the ECL distribution was supposed to be uniform on the micro-sized plates. Therefore, it is highly possible that the observed nonuniform ECL distribution at single nanoplates reflected distinct surface electrocatalytic activities at different sites. Furthermore, ECL microscopy allows continuous in situ imaging, which elucidates the time-varying changes in the spatial distribution of electrocatalytic activity on individual nanoplates, indicating that the corners and edges with more defect sites exhibit higher reactivity, but lower stability than the flat facet. We believe that real-time and high-throughput ECL microscopy may lead to more comprehensive understanding of reactivity patterns of single nanocatalysts.